Extension du domaine de la fête - Tatiana Smirvova; Nicolas Baya-Laffite; Dominique Vinck (Communication)
The Winegrowers’ Festival is a unique traditional festival that has been celebrated in Romandy, Switzerland, since 1797. It takes place in Vevey every 20 to 25 years. Transformations in the media ecosystem are one of the main period markers. Using field research conducted before, during, and after the 2019 celebrations, the authors present the use of YouTube for the event as a novelty in the life of the festival. They look at how the platform, as a space for uploading and engaging with videos produced by both amateurs and institutions, played a role in the organization and experience of the celebrations.